Development and Performance Evaluation of Rice Straw Particleboard Bonded with Chitosan - Peng Luo; Chuanmin Yang; Yan He; Tao Wang (BioResources)
Single-layer particleboards were fabricated from rice straw bonded with chitosan. The rice straw was pre-treated by steam explosion to reduce the extractives and ash contents. The obtained pulp was analyzed for chemical composition, which indicated that the steam explosion pretreatment effectively decreased the extractives and ash contents. The effects of steam explosion pretreatment and chitosan contents on mechanical properties and dimensional stability of rice straw particleboards were explored. The mechanical properties and dimensional stability of particleboards made of steam exploded rice straw showed significant improvement. Addition of chitosan increased the mechanical properties and dimensional stability of particleboards. The mechanical properties and dimensional stability of particleboards improved with the increase of chitosan content.